2008
DOI: 10.2754/avb200877030467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piperonyl Butoxide and Tetramethrin Combinations on Biological Activities of Selected Synthetic Pyrethroid Insecticides against Different Housefly (Musca domestica L., Diptera: Muscidae) Populations

Abstract: Piperonyl butoxide (PBO), a methylenedioxyphenyl compound, is primarily used as a synergist in combination with space spray, residual and admixture products for the control of insect pests in or around domestic and commercial premises, especially food preparation areas. Also, tetramethrin is known as a knockdown agent on target organism and it is generally used with piperonyl butoxide. In this study, effects of piperonyl butoxide and tetramethrin combinations on biological activities of synthetic pyrethroids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
4
11
0
Order By: Relevance
“…These observations are consistent with previous reports on the mode of action and synergist efficacy of PBO [33-36] and agree with a predominant position of PBO in synergizing a wide range of insecticides including organophosphates, carbamates, pyrethrins and pyrethroids [37,38]. Furthermore, high level activity of cytochrome P450s (i.e., MFOs) was detected in most of the An.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with previous reports on the mode of action and synergist efficacy of PBO [33-36] and agree with a predominant position of PBO in synergizing a wide range of insecticides including organophosphates, carbamates, pyrethrins and pyrethroids [37,38]. Furthermore, high level activity of cytochrome P450s (i.e., MFOs) was detected in most of the An.…”
Section: Discussionsupporting
confidence: 92%
“…Because it is known that PBO inhibits P450s that mediate resistance to all classes of insecticides [45,46] and to the well known organochlorine DDT [47,48], our findings suggest that, when this synergist is associated with deltamethrin, it could be efficiently used for malaria vector control interventions as reported in recent studies [49,50]. The potent possibility of PBO as an effective synergist for deltamethrin has also been reported against Aedes and Culex genera, suggesting its wide range of action in several mosquito species [36]. Even though the activity of NSEs was not assessed in the framework of this study, bioassay data revealed that DEF was also an effective synergist to suppress pyrethroid resistance in at least some of the An.…”
Section: Discussionsupporting
confidence: 70%
“…Tetramethrin is used in aerosol formulations, emulsifiable concentrates, and mosquito coils for indoor pest control. 10) Our results clearly support the use of t-t in combination with CP to improve the performance of the mixture significantly. Further studies should evaluate t-t alone against houseflies.…”
Section: Direct Insecticide Spray Effectsupporting
confidence: 71%
“…Previously, the effect of enzyme inhibitors in enhancing insecticide toxicities has been studied in different insect pests. In house flies, for example, the mixture of PBO with different pyrethroids increased the toxicity of cypermethrin, deltamethrin and permethrin [33]. Although PBO is a very good synergist, it should be used cautiously in field due to possible ill effects on non-target organisms.…”
Section: Discussionmentioning
confidence: 99%